A COMPARATIVE STUDY OF THE EFFECT OF MOXONIDINE AND TELMISARTAN ON BLOOD PRESSURE AND INSULIN RESISTANCE IN HYPERTENSIVE PATIENTS - Rajan; Rai, Jaswant; Sandhu, P S (Journal of Drug Delivery and Therapeutics, 2015)
Background: Hypertension being a major cause of cardiovascular diseases worldwide is associated with the overactivation of Renin Angiotensin System (RAS). Both hypertension and insulin resistance are important components of metabolic syndrome and a strong association exists between these two. Some of Previous studies conducted on Moxonidine and Telmisartan suggest, these agents have a better efficacy and safety profile than other antihypertensives The present study is an effort to focus on the effectiveness of these drugs on hypertensive people of Majha region of Punjab, India. Aim: To compare the effects of both drugs as monotherapy on the various parameters of blood pressure, insulin resistance and lipid profile. Material and Methods: It was a randomized (1:1), open label, parallel, comparative study. Moxonidine 0.3 mg in one group (A) (n=30) and telmisartan 40 mg in other group (B) (n=30) were used daily for 12 weeks in hypertensive patients. Patients were evaluated at day 0 and at 12 weeks. Results: Fall in SBP levels by 9.5% in group-A and 7.4% in group-B (p